Polarization Reflector/Color Filter at Visible Frequencies via Anisotropic α‐MoO3. Issue 11 (1st April 2020) - Wei, Chenwei; Abedini Dereshgi, Sina; Song, Xianglian; Murthy, Akshay; Dravid, Vinayak P.; Cao, Tun; Aydin, Koray
Abstract: 2D van der Waals materials have attracted increasing attention in recent years due to their exciting physical properties and offer new opportunities for creating devices with enhanced or novel functionalities. In particular, α‐MoO3 is an emerging member of the fast‐growing 2D family with strong natural anisotropic optical properties. However, anisotropic optical properties of ‐MoO3 in the visible frequency range remain elusive. Here, α‐MoO3 is investigated as an optical material at the visible frequency (450–750 nm), which exhibits a polarization‐dependent complex refractive index due to the anisotropic crystal structure. As a proof of concept, polarization‐sensitive photonic devices including polarization reflectors and polarization color filters are designed and realized by constructing metal–insulator–metal Fabry–Perot cavities. It is observed that resonance frequencies for designed transmission and reflection filters change up to 25 nm with incident polarization which stems from the polarization‐dependent complex refractive indices of α‐MoO3 . The largest contrasts are observed for two orthogonal polarization states parallel to the two orthogonal in‐plane crystal directions. The approach in this study offers new directions for potential applications in the development of polarization‐dependent devices based on 2D van der Waals materials for visible frequencies. Abstract : Anisotropic optical properties of α‐MoO3 with polarization‐dependent complex refractive index in the visible frequency range is reported. Polarization‐sensitive photonic devices, including polarization reflectors and polarization color filters, are designed and realized by constructing Fabry–Perot cavities. Such devices based on α‐MoO3 exhibit lower optical losses and complex nanofabrication are not needed in comparison with the artificial metamaterials.